Small-molecule Ca(V)α(1)⋅Ca(V)β antagonist suppresses neuronal voltage-gated calcium-channel trafficking - Chen, Xingjuan (Proc Natl Acad Sci U S A, 2018)
Extracellular calcium flow through neuronal voltage-gated Ca(V)2.2 calcium channels converts action potential-encoded information to the release of pronociceptive neurotransmitters in the dorsal horn of the spinal cord, culminating in excitation of the postsynaptic central nociceptive neurons. The Ca(V)2.2 channel is composed of a pore-forming α(1) subunit (Ca(V)α(1)) that is engaged in protein–protein interactions with auxiliary α(2)/δ and β subunits. The high-affinity Ca(V)2.2α(1)⋅Ca(V)β(3) protein–protein interaction is essential for proper trafficking of Ca(V)2.2 channels to the plasma membrane. Here, structure-based computational screening led to small molecules that disrupt the Ca(V)2.2α(1)⋅Ca(V)β(3) protein–protein interaction. The binding mode of these compounds reveals that three substituents closely mimic the side chains of hot-spot residues located on the α-helix of Ca(V)2.2α(1). Site-directed mutagenesis confirmed the critical nature of a salt-bridge interaction between the compounds and Ca(V)β(3) Arg-307. In cells, compounds decreased trafficking of Ca(V)2.2 channels to the plasma membrane and modulated the functions of the channel. In a rodent neuropathic pain model, the compounds suppressed pain responses. Small-molecule α-helical mimetics targeting ion channel protein–protein interactions may represent a strategy for developing nonopioid analgesia and for treatment of other neurological disorders associated with calcium-channel trafficking.